DAMPAK HUKUM TERHADAP PENGGUNAAN NARKOTIKA DI KALANGAN PELAJAR KOTA TERNATE - Nam Rumkel; Jamal Hi. Arsyad (Sekolah Tinggi Ilmu Hukum Awang Long, 2018)
Children are the future of the nation, because in its journey is the young generation and the successor to the ideals of the nation's struggle that has a strategic role. As human beings who need to get protection for their rights, at the same time they must also monitor to avoid various things that damage their future, such as being involved in various things that injure their lives such as being involved in Narcotics. Moreover, this was done in his capacity as a student. The development of science is so advanced in various segments of life that it is not only in adults but is almost pervasive among the younger generation, especially students. Therefore, it is the duty of all stakeholders to do things that can be done in order to do understanding and at the same time make prevention with various aspects so that the younger generation will be more specifically students can avoid the dangers that will be caused from the use of narcotics. there is, the study with a model of service that is focused on students at Ternate State High School I (SMA Negeri 1 Ternate) as a partner in exploring more about the impact of drug use. With the hope that this will be a good initial example to do it in another school with the same purpose.